PEMENUHAN HAK SIPIL DAN KEBEBASAN ANAK - Indra Kertati, M.Si (Jurnal Riptek, 2017)
Civil rights and freedom for children have not yet been accepted. Many factors include public ignorance of rights that should exist. Although the Convention on the Rights of the Child has been ratified, it has not been able to implement the rights of the child is still far from expectations. Accessibility of information on the rights of children, still far from reaching, is primarily the provision of basic tools supporting the development of civil rights and freedoms. One of the fundamental rights in civil rights and freedoms is the right to acquire a legal name and recognition of the possession of a birth certificate. The national target in the RPJMD 2019 for the deed coverage is 85%, but there are still many districts that have not yet been realized. Permendagri number 9 of 2016 is a way of accelerating the ownership of Birth Certificate, and the key is how local government to innovate to realize the rights of the child. Semarang City is able to realize with the innovation of online services.